2023
DOI: 10.3389/fonc.2023.1071076
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prognostic factors and construction of prognostic models for triple-positive breast cancer

Abstract: ObjectiveBy identifying the clinicopathological characteristics and prognostic influences of patients with triple-positive breast cancer (TPBC) at Xijing Hospital in China compared with those in the United States, this study aims to construct a nomogram model to forecast the overall survival rate (OS) of TPBC patients.MethodThe Surveillance, Epidemiology, and End Results (SEER) database was used to screen 5769 patients as the training cohort, and 191 patients from Xijing Hospital were used as the validation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Selection of patients in the study. 5.1 months (95% CI: 0-13.0), showing no significance compared with 4.2 months (95% CI: 3.6-4.8) for patients who received everolimus + ET + anti-HER2 drug (p = 0.9). Censoring regimen of tyrosine kinase inhibitor (TKI) combinations, the median PFS for everolimus + chemotherapy + trastuzumab was estimated as 10.9 months (95% CI: 1.5-20.3), better than 3.7 months for everolimus + ET + trastuzumab (95% CI: 1.3-6.2).…”
Section: Choices Of Everolimus-combined Treatment and Associated Prog...mentioning
confidence: 88%
See 4 more Smart Citations
“…Selection of patients in the study. 5.1 months (95% CI: 0-13.0), showing no significance compared with 4.2 months (95% CI: 3.6-4.8) for patients who received everolimus + ET + anti-HER2 drug (p = 0.9). Censoring regimen of tyrosine kinase inhibitor (TKI) combinations, the median PFS for everolimus + chemotherapy + trastuzumab was estimated as 10.9 months (95% CI: 1.5-20.3), better than 3.7 months for everolimus + ET + trastuzumab (95% CI: 1.3-6.2).…”
Section: Choices Of Everolimus-combined Treatment and Associated Prog...mentioning
confidence: 88%
“…4 Several studies have consistently shown that TPBC is highly invasive and exhibits increased proliferative activity. 5,6 TPBC patients generally present with higher tumor grades, larger tumor sizes, and an elevated risk of lymph node metastases. 5 There have been few studies on patients with TPBC, particularly for those at advanced stage disease.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations